Disasters and Development: Natural Disasters, Credit Constraints and Economic Growth - BARRY, FRANK; TOL, RICHARD, S. J.; McDermott, Thomas K. J. (ESRI)
We demonstrate, using a simple two-period equilibrium model of the economy, the potential effects of extreme event occurrences - such as natural or humanitarian disasters - on economic growth over the medium- to long-term. In particular, we focus on the effect of such shocks on investment. We examine two polar cases; an economy in which agents have unconstrained access to capital markets, versus a credit-constrained version, where the economy is assumed to operate in financial autarky. Considering these extreme cases allows us to highlight the interaction of disasters and economic underdevelopment, manifested through poorly developed financial markets. The theoretical analysis shows that the shock of a disaster occurrence could have lasting effects on economic growth only if agents face borrowing constraints. The predictions of our theoretical model are then tested using a panel of data on natural disaster events at the country-year level, covering the period 1979-2007. We find that for countries with low levels of financial sector development, natural disaster events exert a significant negative impact on economic growth. In particular, where access to credit is problematic, the negative effects of disasters on growth are persistent over the medium-term. These results are robust to various checks. Our findings suggest that natural disasters do represent significant threats to economic development in poor countries.
PUBLISHED
Keywords: natural disasters; financial development; credit constraints; economic growth